Structural diversity in serine derived homochiral metal organic frameworks - Kundu, Tanay; Banerjee, Rahul (Journal of Chemical Sciences, 2014)
Two new Zn(II) and Cd(II) based homochiral metal-organic frameworks (MOFs) [SerCdOAc and Zn(Ser)(2)] have been synthesized using pyridyl functionalized amino acid, viz., serine, as an organic linker. The SerCdOAc structure is three dimensional, while that of the Zn(Ser)(2) is two dimensional. The polar voids of the corresponding MOFs are filled with solvent molecules (water in the case of SerCdOAc and methanol in the case of Zn(Ser)(2)). In both cases, metal centres, i.e., Zn(II) and Cd(II), are hexacoordinated. However, with a change in the solvent for synthesis, ligand coordination mode and incorporation of additional coordinated anion resulted in a great change in the final MOF architecture. Herein, for the first time, we could achieve structural variety and synthesize MOFs composed of only metal ion and pyridyl functionalized amino acid linker.
Keywords: Amino acid; crystal engineering; hydrogen bonding; metal organic framework